MENGURAI FENOMENA 'MARRIAGE IS SCARY' DI MEDIA SOSIAL: PERSPEKTIF PERAN PEREMPUAN DALAM ISLAM - Tifanny, Rehilia; Azhari, Putri; Nasution, Aisyah Rizkiah; Apriani, Nur Sakinah; Siregar, Hapni Laila (Universitas Negeri Medan, 2024)
This study focuses on women's perspectives and elaborates on the growing “Marriage is Scary” phenomenon on social media. The research involved female respondents in a survey to learn their perspectives on gender roles in marriage, the risks that may arise, and marriage itself. The results showed that many respondents consider marriage to be an important part of their lives as it can provide emotional support and maintain the purity of the couple. However, bad experiences of others and negative content on social media, such as infidelity and domestic violence, cause fear of marriage.